Prevalence of Sexual Harassment among Female Students of Khulna University - Tuhin Roy; Maleha Binte Rayhan; Rina Aktar (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2023)
In Bangladesh, the scenario of sexual harassment is a great problem in the academic sector as well as the prevalence is equally the same. Female students are the prominent victims of sexual harassment incidents in the educational environment. The main objectives of the study were to evaluate the nature of sexual harassment in academia as well as the impacts on female students and the consequences of the problem. The study was conducted in a qualitative research method and collected primary data with the help of a checklist of the undergraduate students of the Social Science School of Khulna University. Eight respondents and two key informants were selected purposively for the study that fulfilled the criteria of the unit of analysis. The findings of the study disclosed that females are frequent victims of gender-based sexual harassment in the academic sector. Female students constantly face verbal and non-verbal sexual harassment as well as the majority of the respondents don’t disclose or report the incidents to the authority because they cannot rely on perpetrators who will not get proper punishment for their crimes. For this, the victims suffer from various impacts on their mental and physical well-being. As a result, female students replace their career focus, skipping their educational journey and constantly feeling insecure. This research also revealed that society and culture greatly impact sexual harassment occurrences by men. The overall study found the negative impacts of sexual harassment, its consequences along with possible solutions.